Observation of near-interface oxide traps with the charge-pumping technique - Paulsen, Ron (IEEE Electron Device Letters, 1992)
In studies of MOS devices with the charge pumping technique, the authors have encountered a low-frequency increase in the charge recombined per cycle, which they attribute to the charging and discharging of traps located within a tunneling distance of the Si-SiO/sub 2/ interface, i.e., near-interface oxide traps. MOS devices subjected to ionizing radiation as well as ultrathin tunnel oxide polysilicon-oxide-nitride-oxide-silicon (SONOS) nonvolatile memory devices possess a high density of near-interface oxide traps. When the charge recombined per cycle is examined as a function of frequency, a breakpoint is observed at a particular frequency with an inverse equivalent to a trap-to-trap tunneling time constant.